CYBERSPACE AS A PORTRAIT OF EDUCATION INOVATION FOR ISLAMIC BOARDING SCHOOL IN THE SERAMBI MEKAH CITY WEST SUMATERA - Resdilla Pratiwi; Rita Gamasari; Novebri (Universitas PGRI Palembang, 2024)
Cyberspace is examined in this study as an example of innovation in Islamic boarding schools in Veranda of Mecca, Padang Panjang. This study is restricted to six Islamic Boarding Schools located in Padang Panjang: the Padang Panjang Putra Thawalib, the Muhammadiyah Kauman, the Veranda of Mecca Integrated Islamic Boarding School, the Thawalib Putri Islamic Boarding School, and the Puteri Diniyyah College. This study approach makes use of qualitative research, and approaches for observation, documenting, and interviewing are used to acquire data. The findings revealed that a number of Islamic boarding schools made use of cyberspace as a teaching innovation during the pandemic, including the usage of robotics, YouTube, WhatsApp, Zoom, and other social media platforms, in addition to using lab space as a resource for learning innovations. The less competent signal, the fact that some professors still do not grasp technology, and the insufficient internet allowance are some of the suggestions and difficulties that educators and students encounter. Furthermore, a lot of students still do not comprehend distance learning, and there is still a lack of student enthusiasm in studying remotely.